Faba bean root exudates alter pea root colonization by the oomycete Aphanomyces euteiches at early stages of infection. (November 2021) - Laloum, Yohana; Gangneux, Christophe; Gügi, Bruno; Lanoue, Arnaud; Munsch, Thibaut; Blum, Adrien; Gauthier, Adrien; Trinsoutrot-Gattin, Isabelle; Boulogne, Isabelle; Vicré, Maïté; Driouich, Azeddine; Laval, Karine; et al.
Highlights: Pea and faba bean exudation is studied 3 days after Aphanomyces euteiches inoculation. Faba bean exudates have a negative chemotaxis index on A. euteiches zoospores. Furanoacetylenic compounds were only detected in faba bean exudates. Arabinogalactan protein was specifically increased in pea following inoculation. Faba bean root exudates decrease the A. euteiches colonization in pea root. Abstract: Aphanomyces euteiches is an oomycete pathogen that causes the pea root rot. We investigated the potential role of early belowground defense in pea (susceptible plant) and faba bean (tolerant plant) at three days after inoculation. Pea and faba bean were inoculated with A. euteiches zoospores. Root colonization was examined. Root exudates from pea and faba bean were harvested and their impact on A. euteiches development were assessed by using in vitro assays. A. euteiches root colonization and the influence of the oomycete inoculation on specialized metabolites patterns and arabinogalactan protein (AGP) concentration of root exudates were also determined. In faba bean root, A. euteiches colonization was very low as compared with that of pea. Whereas infected pea root exudates have a positive chemotaxis index (CI) on zoospores, faba bean exudate CI was negative suggesting a repellent effect. While furanoacetylenic compounds were only detected in faba bean exudates, AGP concentration was specifically increased in pea.This work showed that early in the course of infection, host susceptibility to A. euteiches is involved via a plant-species specific root exudation opening new perspectives in pea root rot disease management.